2018
DOI: 10.1155/2018/1013978
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electroacupuncture versus Manual Acupuncture through the Expression of TrkB/NF‐κB in the Subgranular Zone of the Dentate Gyrus of Telomerase‐Deficient Mice

Abstract: Our previous study showed that the acupuncture stimulation on the acupoint (ST-36) could activate the brain-derived neurotropic factor (BDNF) signaling pathways in telomerase-deficient mice. Recently, we set out to investigate whether the manual acupuncture (MA) or electroacupuncture (EA) displays a therapeutic advantage on age-related deterioration of learning and memory. Both telomerase-deficient mice (Terc−/− group, n = 24) and wild-type mice (WT group, n = 24) were randomly assigned to 3 subgroups (CON, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…With regard to the difference between the effects of EA and MA on cognitive impairment, it is generally recognized that EA stimulation shows a more beneficial effect on neurodegenerative diseases ( Lin et al, 2018 ). Studies found that EA activated more callback brain regions and functional connectivity than MA ( Liu et al, 2023 ) due to the electrical twitching of surrounding tissues it produced ( Yamamoto et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the difference between the effects of EA and MA on cognitive impairment, it is generally recognized that EA stimulation shows a more beneficial effect on neurodegenerative diseases ( Lin et al, 2018 ). Studies found that EA activated more callback brain regions and functional connectivity than MA ( Liu et al, 2023 ) due to the electrical twitching of surrounding tissues it produced ( Yamamoto et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, MA and EA might exert different therapeutic effects through respective mechanisms related to the characteristics of diseases ( Yu et al, 2014 ). For example, ( Lin et al, 2018 ) pointed out that EA might promote neuroprotection and neuronal regeneration through TrkB and NF-kB signal pathways, while MA could activate the BDNF and its downstream signaling pathways ( Ferrón Sacri et al, 2009 ). Second, the effect of MA depends on acupuncture points, stimulating intensity ( Jiang et al, 2013 ) and courses of treatment, as well as the “De-Qi” feeling ( Lin et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of acupuncture can be further enhanced by electrical stimulation or manual manipulation. Electroacupuncture is believed to be more repeatable, and more effective in ameliorating the spatial learning and memory capability (49). The parameters of electroacupuncture, including waveform and frequency, are also important factors influencing treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Because the stimulation parameters are easily controlled and the stimulation models are correspondingly stable, the clinical application of electroacupuncture stimulation (EAS) has become popular (Napadow et al, 2005;Zhang et al, 2014a). A number of studies have confirmed that EAS produces better subjective evaluations of treatment effects than traditional acupuncture (Lin et al, 2018;Schliessbach et al, 2011).…”
Section: Introductionmentioning
confidence: 99%